CGG repeat length and AGG interruptions as indicators of fragile X–associated diminished ovarian reserve. (September 2018) - Lekovich, Jovana; Man, Limor; Xu, Kangpu; Canon, Chelsea; Lilienthal, Debra; Stewart, Joshua; Pereira, Nigel; Rosenwaks, Zev; Gerhardt, Jeannine
Abstract Purpose Fragile X premutation (PM) carriers may experience difficulties conceiving a child probably due to fragile X–associated diminished ovarian reserve (FXDOR). We investigated which subgroups of carriers with a PM are at higher risk of FXDOR, and whether the number of AGG interruptions within the repeat sequence further ameliorates the risk. Methods We compared markers of ovarian reserve, including anti-Müllerian hormone, antral follicle count, and number of oocytes retrieved between different subgroups of patients with a PM. Results We found that carriers with midrange repeats size (70–90 CGG) demonstrate significantly lower ovarian reserve. Additionally, the number of AGG interruptions directly correlated with parameters of ovarian reserve. Patients with longer uninterrupted CGG repeats post–AGG interruptions had the lowest ovarian reserve. Conclusion This study connects AGG interruptions and certain CGG repeat length to reduced ovarian reserve in carriers with a PM. A possible explanation for our findings is the proposed gonadotoxicity of theFMR1 transcripts. Reduction of AGG interruptions could increase the likelihood that secondary RNA structures in theFMR1 messenger RNA are formed, which could cause cell dysfunction within the ovaries. These findings may provide women with guidance regarding their fertility potential and accordingly assist with their family planning.